2001
DOI: 10.1046/j.1468-3148.2001.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Dissemination of Active Support Training and Training Trainers

Abstract: The aim of the present study was to replicate active support (AS) and train the service managers of community housing services as trainers in so doing. Training was conducted in three phases: (1) in 22 houses, it was led by one of the researchers, with identified managers assisting (Apprenticeship); (2) in 16, it was led by a manager who had participated in the previous phase, assisted by the researcher (Supervision); and (3) in 36 houses, it was undertaken independently by managers who had participated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
154
2
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(168 citation statements)
references
References 30 publications
6
154
2
6
Order By: Relevance
“…In contrast, the increase in staff reporting no training in active support in Organisation 2 could be linked to the decline in active support. Although not many staff reported hands-on training (which had been found to be important in other studies such as Jones, Felce, Lowe, Bowley, Pagler, Gallagher, et al, 2001;Jones, Felce, Lowe, Bowley, Pagler, Strong, et al, 2001), those that did were more likely to be working in services where active support was good. A possible confounding factor is that not all organisations directly labelled training as active support although active support principles were included in training as part of an overall practice framework.…”
Section: What Might Be Needed For Successmentioning
confidence: 91%
See 2 more Smart Citations
“…In contrast, the increase in staff reporting no training in active support in Organisation 2 could be linked to the decline in active support. Although not many staff reported hands-on training (which had been found to be important in other studies such as Jones, Felce, Lowe, Bowley, Pagler, Gallagher, et al, 2001;Jones, Felce, Lowe, Bowley, Pagler, Strong, et al, 2001), those that did were more likely to be working in services where active support was good. A possible confounding factor is that not all organisations directly labelled training as active support although active support principles were included in training as part of an overall practice framework.…”
Section: What Might Be Needed For Successmentioning
confidence: 91%
“…The evidence base spans four decades, involves at least 1400 people, uses different methodologies, in different countries, in different settings and involves different research teams and training approaches. Studies of effectiveness have ranged from small-scale pre-post training comparisons through to larger scale observational studies (see Bigby & Beadle-Brown, 2016;Jones, Felce, Lowe, Bowley, Pagler, Gallagher, et al, 2001;Jones, Felce, Lowe, Bowley, Pagler, Strong, et al, 2001;.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were drawn from four studies on staffed group homes (Felce et al , 2003Jones et al 2001 [baseline data only]; Perry and Felce 2005) and a fifth study established through collaboration with 44 local primary health service providers (Baxter et al 2006). Participants were on average 44.5 years of age (range 18-90 years, SD 14.6), 52.7% were male and 34.3% were assessed as having the triad of impairments characteristic of ASD (N = 281).…”
Section: Participantsmentioning
confidence: 99%
“…Staff receive training in developing person-centred activity plans for those in their care and receive coaching on how to encourage them to engage in activities to deflect them from challenging behaviour. Trials (mainly small case studies) have shown contrasting results, including no effect (Jones 2001;Stancliffe 2008), a decrease in challenging behaviour (Toogood 2009) and an increase in challenging behaviour (Bradshaw 2004). Further evaluation of active support is warranted.…”
Section: Social Interventionsmentioning
confidence: 99%